Existence, Uniqueness, and Stability Solutions of Nonlinear System of Integral Equations - Rizgar Issa Hasan (Jurnal Matematika MANTIK, 2020)
The aim of this work is to study the existence, uniqueness, and stability solutions of a new nonlinear system of integral equation by using Picard approximation (successive approximation) method and Banach fixed point theorem. The study of such nonlinear integral equations is more general and leads us to improve to extend the result of Butris. Theorems on the existence and uniqueness of a solution are established under some necessary and sufficient conditions on closed and bounded domains (compact spaces).